Ethics Briefing - Norcliffe-Brown, Dominic (Journal of medical ethics, 2020)
At the time of writing the COVID-19 pandemic was entering its ninth month, with nearly 800 000 recorded fatalities and 22 million infections in 188 countries and territories.1 In previous ethics briefings2 we raised concerns about the possibility that demand for life-sustaining treatment would overwhelm supply, with a consequent requirement for health professionals to make challenging triage decisions. Fortunately, to date, these have largely not been realised, although there is a possibility that countries in which containment measures have been less-successful, such as South Africa, may still be required to triage.3 Despite the successful ‘flattening of the curve’ in many countries, there is a wide consensus that we remain firmly within the pandemic. Enormous practical challenges remain. It is unclear whether the pandemic will ultimately take the form of two or more successive waves, or whether the patchwork of global responses will lead to a sustained slow ‘burn’ with sporadic flare-ups.4 Areas of uncertainty include whether infection confers some immunity, how long any such immunity might last, whether effective vaccines can be developed and if seasonal temperature fluctuations alter the spread of the virus. The pandemic will also be fundamentally shaped by the decisions that governments make and the extent to which their diktats are complied with by citizens.With the - possibly temporary - retreat of urgent clinical ethics issues, such as triage, opportunities have arisen to reflect on some of the ethical questions that underlie and structure the demanding policy decisions that governments are wrestling with. One of the early questions was how to balance the complex constellation of costs and benefits associated with lockdown. Countries that …